Late recovery of awareness in prolonged disorders of consciousness –a cross-sectional cohort study. Issue 20 (25th September 2018) - Yelden, Kudret; Duport, Sophie; James, Leon M.; Kempny, Agnieszka; Farmer, Simon F.; Leff, Alex P.; Playford, E. Diane
Abstract: Purpose: To detect any improvement of awareness in prolonged disorders of consciousness in the long term. Methods : A total of 34 patients with prolonged disorders of consciousness (27 vegetative state and seven minimally conscious state; 16 males; aged 21–73) were included in the study. All patients were initially diagnosed with vegetative/minimally conscious state on admission to our specialist neurological rehabilitation unit. Re-assessment was performed 2–16 years later using Coma Recovery Scale-Revised. Results: Although remaining severely disabled, 32% of the patients showed late improvement of awareness evidenced with development of non-reflexive responses such as reproducible command following and localization behaviors. Most of the late recoveries occurred in patients with subarachnoid hemorrhage (5/11, 45.5%). The ages of patients within the late recovery group (Mean = 45, SD = 11.4) and non-recovery group (Mean = 43, SD = 15.5) were not statistically different ( p  = 0.76). Conclusions: This study shows that late improvements in awareness are not exceptional in non-traumatic prolonged disorders of consciousness cases. It highlights the importance of long-term follow up of patients with prolonged disorders of consciousness, regardless of the etiology, age, and time passed since the brain injury. Long-term follow up will help clinicians to identify patients who may benefit from further assessment and rehabilitation. Although only one patient achieved recovery of function, recovery of awareness may have important ethical implications especially where withdrawal of artificial nutrition and hydration is considered. Implications for rehabilitation: Long-term regular follow-up of people with prolonged disorders of consciousness is important. Albeit with poor functional outcomes late recovery of awareness is possible in both traumatic and non-traumatic prolonged disorders of consciousness cases. Recovery of awareness has significant clinical and ethical implications especially where withdrawal of artificial nutrition and hydration is considered.